Improving the Efficacy of Quinolylnitrones for Ischemic Stroke Therapy, QN4 and QN15 as New Neuroprotective Agents after Oxygen-Glucose Deprivation/Reoxygenation-Induced Neuronal Injury - José M. Alonso; Alejandro Escobar-Peso; Israel Fernández; Alberto Alcázar; José Marco-Contelles (MDPI AG, 2022)
In our search for new neuroprotective agents for stroke therapy to improve the pharmacological profile of the compound quinolylnitrone QN23, we have prepared and studied sixteen new, related and easily available quinolylnitrones. As a result, we have identified compounds QN4 and QN15 as promising candidates showing high neuroprotection power in a cellular experimental model of ischemia. Even though they were found to be less active than our current lead compound QN23, QN4 and QN15 provide an improved potency and, particularly for QN4, an expanded range of tolerability and improved solubility compared to the parent compound. A computational DFT-based analysis has been carried out to understand the antioxidant power of quinolylnitrones QN23, QN4 and QN15. Altogether, these results show that subtle, simple modifications of the quinolylnitrone scaffold are tolerated, providing high neuroprotective activity and optimization of the pharmacological potency required for an improved design and future drug developments in the field.